2015
DOI: 10.1519/jsc.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Strongman vs. Traditional Resistance Training Effects on Muscular Function and Performance

Abstract: Currently, no evidence exists as to the effectiveness of strongman training programs for performance enhancement. This study compared the effects of 7 weeks of strongman resistance training vs. traditional resistance training on body composition, strength, power, and speed measures. Thirty experienced resistance-trained rugby players were randomly assigned to one of the 2 groups; strongman (n = 15; mean ± SD: age, 23.4 ± 5.6 years; body mass, 91.2 ± 14.8 kg; height, 180.1 ± 6.8 cm) or traditional (n = 15; mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Between-group differences indicated small positive changes in muscle mass in the strongman group compared with the traditional group, indicating strongman training may be a viable modality of training for the hypertrophy block of training (40).…”
Section: Practical Applicationsmentioning
confidence: 94%
See 1 more Smart Citation
“…Between-group differences indicated small positive changes in muscle mass in the strongman group compared with the traditional group, indicating strongman training may be a viable modality of training for the hypertrophy block of training (40).…”
Section: Practical Applicationsmentioning
confidence: 94%
“…It is acknowledged that the majority of existing studies in the field of strongman training is on acute responses with a lone study on shortterm training (40). For more in-depth practical applications, strongman training would need to be researched with the use of training studies, examining the chronic effects over a period of months to years.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Strongman exercises and equipment have gained increasing popularity with strength and conditioning (S&C) coaches due to being versatile and inexpensive [ 1 , 2 , 3 ]. Winwood et al [ 4 ] surveyed 220 S&C coaches on their professional practice, in which 193 reported using strongman implements, with the most commonly used equipment being tyres, sleds, ropes, kettlebells, sandbags and farmer’s walk bars. Justifications for using strongman equipment were for anaerobic and metabolic conditioning, and strength, power and muscular endurance development.…”
Section: Introductionmentioning
confidence: 99%
“…Push pressing with a strongman log is being increasingly included in athlete strength and conditioning programs and in research (12,13,14,15). The principal reason for this is that it is thought that it makes greater mechanical demands on the athlete in terms of mid-section and shoulder girdle stability.…”
Section: Introductionmentioning
confidence: 99%